The subtle balance of weak supramolecular interactions: The hierarchy of halogen and hydrogen bonds in haloanilinium and halopyridinium salts - Raatikainen, Kari; Cametti, Massimo; Rissanen, Kari (Beilstein Journal of Organic Chemistry, 2010)
The series of haloanilinium and halopyridinium salts: 4-IPhNH3Cl (1), 4-IPhNH3Br (5), 4-IPhNH3H2PO4 (6), 4-ClPhNH3H2PO4 (8), 3-IPyBnCl (9), 3-IPyHCl (10) and 3-IPyH-5NIPA (3-iodopyridinium 5-nitroisophthalate, 13), where hydrogen or/and halogen bonding represents the most relevant non-covalent interactions, has been prepared and characterized by single crystal X-ray diffraction. This series was further complemented by extracting some relevant crystal structures: 4-BrPhNH3Cl (2, CCDC ref. code TAWRAL), 4-ClPhNH3Cl (3, CURGOL), 4-FPhNH3Cl (4, ANLCLA), 4-BrPhNH3H2PO4, (7, UGISEI), 3-BrPyHCl, (11, CIHBAX) and 3-ClPyHCl, (12, VOQMUJ) from Cambridge Structural Database for sake of comparison. Based on the X-ray data it was possible to highlight the balance between non-covalent forces acting in these systems, where the relative strength of the halogen bonding C–X···A− (X = I, Br or Cl) and the ratio between the halogen and hydrogen bonds [C–X···A− : D–H···A−] varied across the series.
Keywords: crystal engineering; halogen bonding; hydrogen bonding; supramolecular chemistry; weak interactions